PENGARUH SOCIAL PRESENCE TERHADAP PERILAKU PEMBELIAN IMPULSIF PADA SIARAN LANGSUNG TIKTOK DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi pada Merek Somethinc) - Nadia Aqilah, Nadia Aqilah; Dirgantara, I Made Bayu; Aryandika, Ardiaz Ajie (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The rapid rise in popularity of live streaming prompted the development of a new business strategy called live streaming commerce. The presence of high interactivity and rich sensory stimulation on live streaming affects consumer trust so that it easily encourages impulsive buying behavior. However, knowledge about impulse buying in live streaming commerce is very limited. This study proposes a theoretical framework that can be used to examine how live streaming influence consumers' impulse buying intentions. The population in this study are TikTok users who know and have purchased Somethinc products in live streaming commerce. In an online survey by distributing questionnaires, 153 valid answers were obtained which were selected by purposive sampling. The data obtained were then analyzed using structural equation modeling (SEM). The results show that the 3 dimensions of social presence (social presence of platforms, viewers and live streamers) have a positive effect on consumer trust. The results also show that the 3 dimensions of social presence (social presence of platforms, viewers, and live streamers) have a positive effect on impulsive buying behavior through consumer trust. Furthermore, this study proves that impulse buying is driven by social presence and consumer trust in the context of live streaming commerce. This research will help brands to better understand how to stimulate consumer buying behavior. Research also provides a reference for developing live streaming commerce in online business